Efeitos do reforçamento não contingente com estímulos competitivos e funcionalmente equivalentes no comportamento autolesivo no TEA - Souza, Henrique Carlos de (2025)
This study investigated the effects of continuous non-contingent reinforcement (NCR) with competing (COMP) and functionally equivalent (EQUIV) stimuli in reducing selfinjurious behavior (SIB) in individuals with autism spectrum disorder (ASD), aiming to verify the efficacy of these stimuli in decreasing the frequency of SIB maintained by automatic reinforcement. Three male participants diagnosed with ASD were recruited and submitted to a reversal experimental design. Initially, brief functional analysis was performed to determine the conditions maintaining SIB. Then, continuous NCR sessions were conducted with competing (highly preferred toys with reinforcing function) and functionally equivalent (tactile stimuli similar to self-injury) stimuli. The occurrence of SIB was recorded in different experimental phases and compared to the baseline. The results indicated that the procedures reduced the frequency of SIB compared to baseline. NCR with competitive stimuli showed significant initial efficacy but lost its effect over time. NCR with functionally equivalent stimuli demonstrated greater stability in reducing SIB, which suggests that sensory similarity between the stimulus and the self-injurious behavior may increase the efficacy of the intervention, but not as an equivalent stimulus. The results reinforce the importance of individualized strategies in the treatment of SIB in the context of ASD